Meningkatkan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Problem Based Learning pada Mata Pelajaran Pendidikan Agama Katolik Materi Aku Pribadi Unik Kelas IV SDN 2 Nainggolan Tahun Pelajaran 2024/2025 - Tiorisma Sinaga (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The low learning outcomes of students can be attributed to various issues that often arise during the classroom learning process. In Catholic Religious Education, the low performance is indicated by the pre-test scores that did not meet the minimum passing criteria (KKM), with only 47.27% of students, or 11 students, failing to achieve the expected scores. The teaching method used by the teacher was predominantly lecture-based, which resulted in low student participation, with the majority of students being passive and only a small number actively engaging in the learning activities. Based on these issues, this research poses the question: "Can the implementation of the Problem Based Learning (PBL) model improve the learning outcomes of students in Catholic Religious Education and Character Education in Grade IV at SDN 2 Nainggolan for the 2023/2024 academic year?" The aim of this study is to provide a clear understanding of how the PBL model can enhance student learning outcomes in the subject. This research is Classroom Action Research (CAR) aimed at determining the improvement in student learning outcomes through the application of the Problem Based Learning (PBL) model. The researcher acted as the teacher, while the Grade IV teacher served as a collaborative partner and observer. The learning process was conducted over two cycles, with each cycle consisting of planning, action implementation, observation, and reflection. Data were collected through the observation of student and teacher activities, student learning outcome tests, and documentation. In the first cycle, student learning outcomes showed improvement, with 8 students meeting the minimum passing criteria (KKM) and the highest score being 90. The test was continued in the second cycle with some minor adjustments, and the results showed further improvement, with 11 students meeting the KKM and the highest score remaining 90. Based on the findings of this research, it can be concluded that the application of the Problem Based Learning (PBL) model can improve student learning outcomes in Catholic Religious Education for Grade IV. The mastery of student learning outcomes in the first cycle reached 72.72% according to the post-test results, and increased to 86.36% in the second cycle, indicating an improvement of 13.64%. Therefore, it can be concluded that if the PBL model is applied effectively and consistently, it will improve student learning outcomes.